The effect of different term swimming exercise in rats on serum leptin levels: Effect of different term exercise on leptin - Acar, Hakan; Tutkun, Erkut (Progress in Nutrition, 2020)
The aim of this study was to investigate the effect of serum leptin in rats performing various durationswimming exercises. In the study, 30 healthy albino wistar male rats with an average weight of 180-220grams were divided into 5 groups including; control, water exercises, 15, 30 and 60 minutes swimming groups.Animals were swim-exercised for 90 days. At the end of 90 days, after performed urethane anesthesia, bloodsamples were taken by intracardiac way. Collected blood was analysed according to procedures. Data wereanalyzed by using SPSS 15. One-way anova and tukey multiple comparison test were performed in the study.The homogeneity of the variances was examined by Levene’s statistic. Results showed that the leptin levelswere as follows: control (1480,00 pg/ml), water exercise (705,83 pg/ml), 15 (602,33 pg/ml), 30 (396,67 pg/ml) and 60 (435,83 pg/ml). Statistically significant difference was found between control and 30 minutesswimming group (p=0,012) and control and 60 minutes swimming group (p=0,017) (p